2021
DOI: 10.3390/ijms22084049
|View full text |Cite
|
Sign up to set email alerts
|

STAT6 Is Critical for the Induction of Regulatory T Cells In Vivo Controlling the Initial Steps of Colitis-Associated Cancer

Abstract: Inflammation is the main driver of the tumor initiation and progression in colitis-associated colorectal cancer (CAC). Recent findings have indicated that the signal transducer and activator of transcription 6 (STAT6) plays a fundamental role in the early stages of CAC, and STAT6 knockout (STAT6−/−) mice are highly resistant to CAC development. Regulatory T (Treg) cells play a major role in coordinating immunomodulation in cancer; however, the role of STAT6 in the induction and function of Treg cells is poorly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
(36 reference statements)
1
12
0
1
Order By: Relevance
“…Therefore, all these variations helped improve the inflammation, in line with other studies. Also, other investigators showed that increased STAT6 could play a significant role in colitis by affecting the IL-13 production [ 23 ], whereas a decrease in STAT6 could prevent apoptosis and disruption of cell membrane integrity [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, all these variations helped improve the inflammation, in line with other studies. Also, other investigators showed that increased STAT6 could play a significant role in colitis by affecting the IL-13 production [ 23 ], whereas a decrease in STAT6 could prevent apoptosis and disruption of cell membrane integrity [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our polyclonal activation assay, stimulation of total T cells under TH0 conditions in the absence of exogenous IL-4 induced phosphorylation of STAT6, likely due to the activation of infrequent IL-4–producing cells. Elevated pSTAT6 during T cell activation under nonpolarizing conditions has been shown to play an important role in T cell differentiation, such as the downregulation of TCF1 ( 30 ) and maintaining IRF4 ( 28 ) and FOXP3 ( 40 , 41 ) expression. Our experiments in the LCMV infection model showed that STAT6 inhibition upregulated the expression of CD39 on LCMV-specific SMARTA cells, providing additional evidence that the IL-4-STAT6-GATA3 pathway is activated and relevant in antiviral responses in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Signal transducer and activator of transcription 6 (STAT6) participates in the cellular response to IL‐4 and IL‐13, which generate CD4+ Th2 cells. Our previous studies have demonstrated that STAT6 is an essential regulator of Tregs’ function during colitis‐associated colorectal cancer (CAC) [8]. STAT6 knockout (STAT6‐/‐) mice are highly resistant to CAC development and present a high number of CD4+Foxp3+CD25+ cells in the colon, circulation, and spleen, including over‐expressions of TGF‐β, IL‐10, and Foxp3, compared with wild‐type (WT) mice, during the early stages of CAC development [8].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have demonstrated that STAT6 is an essential regulator of Tregs' function during colitis-associated colorectal cancer (CAC) [8]. STAT6 knockout (STAT6-/-) mice are highly resistant to CAC development and present a high number of CD4+Foxp3+CD25+ cells in the colon, circulation, and spleen, including over-expressions of TGF-β, IL-10, and Foxp3, compared with wild-type (WT) mice, during the early stages of CAC development [8]. The increased frequency of Tregs during STAT6 deficiency coincided with minor intestinal damage, decreased cell proliferation in the early stages of injuryinduced tumor formation, and increased apoptosis in advanced tumors [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation